Validación del proceso de limpieza en el equipo de envasado de polvos estériles para cloranfenicol succinato sódico - Rosado Alvino, Anali Pilar (2008)
The validation of the process of cleaning in the equipment of sterile powder packaging for Chloranphenicol Succinato Sodico, was made in the pharmaceutical laboratory Corporacion Infarmasa S.A., during the months of January to February of the 2008. The purpose of this study was the Validation of the Process of Cleaning to guarantee of this way that the plans of this one product are below the found acceptable limit. In order to fulfill our objective we used hisopos contained in test tubes with desionizada water, which served us to make the hisopado one in the different tactically important points in the equipment, quantifying itself soon by means of the espectrofotométrico method. The collected data were process by means of the statistical analysis Anova (Analysis of variance), to verify the variability between lots. The study allowed to demonstrate that the plans of Cloranfenicol Succinato Sódico in the equipment of sterile powder packaging were below the acceptance limit, obtaining therefore a result us as, considering themselves of this one validated way, but with significant variability between lots.